2001
DOI: 10.1080/00016480127368
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided Surgery of the Anterior Skull Base

Abstract: Minimally invasive surgical procedures have revolutionized surgery of the paranasal sinuses. The endonasal procedure has become standard practice due to a better understanding of pathological physiology. However, malformations, previous operations and bleeding can interfere greatly with intraoperative orientation. Together with microscopy and endoscopy, image-guided surgery has the potential to be of significant assistance to the surgeon. We evaluated the electromagnetic navigation system InstaTrak 2000 (Visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[4] However, previous operations, anatomical variations, and invasion of surrounding structures may critically interfere with intraoperative orientation, thus exposing the patient to greater risk. [6]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] However, previous operations, anatomical variations, and invasion of surrounding structures may critically interfere with intraoperative orientation, thus exposing the patient to greater risk. [6]…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, proper training is necessary for the personnel in the operating room. [6] Furthermore, the technology may necessitate a larger operating room and rearrangement of other equipments in the room. This is especially salient when working with optical systems which require a clear line of sight between the infrared camera, reference arch, and pointer instruments, or with the magnet system which requires a clear magnetic field free of other metals that can cause interference.…”
Section: Discussionmentioning
confidence: 99%
“…Such lesions are particularly challenging to access endonasally due to the proximity of critical neurovasculature, including the carotid arteries and cranial nerves [2]. Due to the complexity of these surgeries, navigation systems are often used to assist the surgeon [3], and studies have shown that navigation helps reduce the morbidity of the endonasal approach [4], [5]. Active research continues to improve the accuracy of the navigation systems [6]–[8] and reports that current less invasive registration methods, e.g., surface tracing, are not sufficient for all skull base procedures.…”
Section: Introductionmentioning
confidence: 99%